Microalgae biomass: A multi-product biorefinery solution for sustainable energy, environmental remediation, and industrial symbiosis - Mahmod, Safa Senan; AL-Rajabi, Maha Mohammad; Abdul, Peer Mohamed; Ding, Gongtao; Kamrul Fakir, Kamarudin; Gunny, Ahmad Anas Nagoor; Jian-Ping, Tan; Mohd Sobri, Takriff (Elsevier B.V., 2025)
The rapid expansion of industrialization and the depletion of non-renewable fossil fuel have urged the search for alternative and sustainable renewable resources to fulfil the escalating energy demand while reducing water pollution and greenhouse gas emissions. Microalgae have emerged as a promising and sustainable solution, capable of not only treating wastewater but also yielding valuable products. This study aimed to explore the primary applications of microalgae, including wastewater treatment and CO2 sequestration, while assessing the viability of utilizing the resultant microalgae biomass (MB) across diverse sectors such as liquid and gaseous biofuels, bioplastics, animal and aquatic feed, nutraceuticals and pharmaceuticals, biofertilizers, and cosmetics production. Additionally, the study discusses the importance of assessing the environmental impacts of these applications through life cycle assessment (LCA) studies and elaborate the concept of a multi-products biorefinery system. To address the contemporary challenges of the bio-economy in simultaneously producing multiple high-value products, the biorefinery complexity index (BCI) was estimated to be 37, highlighting the need for further research to establish the practicability of a multi-products biorefinery system.